Edible antimicrobial coating on carrot (Daucus carota L.) slices - Morales, Maria Lorina Celestino (2010.)
ABSTRACT This research aimed to characterize and evaluate the effects of carrageenan-based edible antimicrobial coating on carrot slices. Sorbic acid was the antimicrobial used. In order to determine the best combination of coating components, nine treatments with different compositions containing carrageenan and sorbic acid were used to coat the samples. Physicochemical and microbiological analyses were conducted and it was observed that samples coated with 0.5% carrageenan with 0.1% sorbic acid showed the least evidence of deterioration or spoilage. This coating was chosen as the optimum level and was used for three runs to assess its repeatability. Results on the test for % weight loss, total soluble solids, water activity and pH during a 12-day storage period under refrigeration showed no significant differences (P>0.05) between the three runs. After 12 days of storage under refrigeration, the Aerobic Plate Count obtained ranged from 4.13-4.16 log CFU/g and mold counts obtained were less than 3 log CFU/g, showing the effectiveness of the carrageenan-sorbic acid edible coating in delaying the deterioration of carrot slices.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Carrots; Vegetables -- Preservation